1994
DOI: 10.1099/00207713-44-1-15
|View full text |Cite
|
Sign up to set email alerts
|

Intrageneric Structure of the Genus Rhodobacter: Transfer of Rhodobacter sulfidophilus and Related Marine Species to the Genus Rhodovulum gen. nov.

Abstract: Phylogenetic relationships among species of the genus Rhodobacter and related taxa were elucidated by studying 16s rRNA sequence information and genomic DNA homology data. The 16s rRNA gene was amplified by the PCR and was sequenced directly by a combined method consisting of cycle sequencing and automated fluorescence detection. Pairwise sequence comparisons and a distance matrix analysis showed that the Rhodobacter species could be divided into two major clusters; one cluster included the freshwater and terr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
75
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(79 citation statements)
references
References 38 publications
4
75
0
Order By: Relevance
“…S. lacuscaerulensis is a long (9-18 mm), non-motile, catalasepositive, gas vacuole-containing rod that grows optimally at 45 uC (Petursdottir & Kristjansson, 1997). R. sulfidophilum is a facultative anaerobic phototrophic organism that contains bacteriochlorophyll a (Hiraishi & Ueda, 1994). Therefore, strain HTCC2503 T cannot be identified as a member of any of the genera described above.…”
Section: Polyphasic Taxonomy Of the Novel Strainsmentioning
confidence: 99%
“…S. lacuscaerulensis is a long (9-18 mm), non-motile, catalasepositive, gas vacuole-containing rod that grows optimally at 45 uC (Petursdottir & Kristjansson, 1997). R. sulfidophilum is a facultative anaerobic phototrophic organism that contains bacteriochlorophyll a (Hiraishi & Ueda, 1994). Therefore, strain HTCC2503 T cannot be identified as a member of any of the genera described above.…”
Section: Polyphasic Taxonomy Of the Novel Strainsmentioning
confidence: 99%
“…Comparisons of rRNA, i.e., DNA-rRNA hybridization and 16s rRNA cataloging and sequencing, have demonstrated that these bacteria belong to several different lines of descent within the alpha-2 subclass of the Proteobacteria (2,33,34). Exceptionally, Rhodopseudomonas blastica is a member of the alpha-3 subclass, closely related to Rhodobacter species (14,18), and this situation has led to the proposal for transfer of R. blastica to the genus Rhodobacter (18). The phenotypic and chemotaxonomic heterogeneity in the genus Rhodopseudomonas has been summarized by Imhoff et al (16).…”
mentioning
confidence: 99%
“…R. sulfidophilum, formerly known as Rhodobacter sulfidophilus [13], was supplied as R. sulfidophilus (DSM Strain 1374 T ) by the Deutsche Sammlung von Mikroorganismen und Zellkulturen GmbH, Braunschweig, Germany. It was maintained by growing aerobically in the dark in liquid culture with sub-culturing every five days in a modified Erythrobacter medium of Shioi [14] supplemented with glucose (2.0 g/l), malate (6.0 g/l) and nicotinic acid (2.0 mg/l) and biotin (0.02 mg/l): ferric citrate in the original medium was replaced with ferric-ammonium citrate.…”
mentioning
confidence: 99%